Accelerator impact on peer networking: Examining the formation, use, and development of inter-organizational networks among early-stage start-ups - Hannah Franziska Gundel (Junior Management Science (JUMS), 2024)
Developing, promoting, and managing networks is a core element of entrepreneurship. Yet, limited research exists on the inherent processes and interaction dynamics underlying the social phenomenon of network formation among nascent companies over time. I conducted a qualitative inductive study with ten founding teams over three months to gain new theoretical insights into inter-organizational network formation among early-stage start-ups in an accelerator environment. The systematically derived dynamic process model proposes a framework capturing different types of peer relationships that change in response to founders' shifting personal and organizational needs over time. It highlights the accelerator's intermediary role in orchestrating network formation among founders through strategic design choices and regulatory program structure, establishing a collectivist organizational culture. Findings point to the entrepreneur's particular context in identifying relevant collaboration opportunities and navigating effective start-up networks, significantly informing the entrepreneurial career trajectory. The theoretical framework offers guidance for ecosystem builders, policy makers as well as opens possibilities for further research in social science and the entrepreneurial landscape.
Keywords: 650; accelerator; entrepreneurial networking; inter-organizational networks; network orchestration; peer networks